Supply Chain Management Model in Digital for One Tampon One Product Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim were to design and to assess supply chain management model in digital for one Tampon one product management in Thailand. The sample groups were five experts in supply chain , five experts in education technology. The paper sample totalling ten experts. The paper tool was evaluation form to evaluate supply chain management model in digital for one Tampon one product management in Thailand comprises nine components, namely main components, Supplier, OTOP firms, Outlet . wholesaler, Retailer, Customer Satisfaction and Return. The data analysed by using arithmetic mean and standard deviation. supply chain management model in digital for one Tampon one product management in Thailand using Back-Box technique. The results from experts agreement of supply chain management model in digital for one Tampon one product management in Thailand that mean the model may be applie in support the tasks.